Order of Things - "Foucault, Michel" (New York, 2003)
When one defines "order" as a sorting of priorities, it becomes beautifully clear as to what Foucault is doing here. With virtuoso showmanship, he weaves an intensely complex history of thought. He dips into literature, art, economics and even biology in The Order of Things, possibly one of the most significant, yet most overlooked, works of the twentieth century. Eclipsed by his later work on power and discourse, nonetheless it was The Order of Things that established Foucault's reputation as an intellectual giant. Pirouetting around the outer edge of language, Foucault unsettles the surface of literary writing. In describing the limitations of our usual taxonomies, he opens the door onto a whole new system of thought, one ripe with what he calls "exotic charm". Intellectual pyrotechnics from the master of critical thinking, this book is crucial reading for those who wish to gain insight into that odd beast called Postmodernism, and a must for any fan of Foucault.
Keywords: Philosophy